PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP KINERJA PEGAWAI DINAS PERKEBUNAN DAN KEHUTANAN KABUPATEN LANDAK - B11110136, DINATA LISA (Jurnal Manajemen Update, 2014)
To the effect of observational it is subject to be know that transformasional's leadership style and transactional, clerk performance and if transformasional's leadership and transactional carries the wind on duty having for to clerk performance on duty plantation and forest is porcupine regency. Question that is proposed in this research is what inspire transformasional's leadership and transactional carries the wind on duty get to regard clerk performance. Research is done at on duty plantation and kehutanan is porcupine regency. Available 74 respondent those are taken by use of census research model. Observational type is survey, descriptive and kausal. Downloading model is analisis linear bifilar. Result tests f and point out that as big as 185%. transformasional's leadership style and transactional carries the wind on duty ascendant to clerk performance on duty plantation and forest is porcupine and point regency p< 0,05 one mean that Ho is refused and Ha is accepted, where is Ha is styled transformasional's leadership and transactional carries the wind on duty ascendant to clerk performance. Available in quiz t found that partially good styled transformasional's leadership and transactional communicates signifikan with clerk performance on duty plantation and kehutanan. It pointed out by probalitas's point variable second smaller of 0,05 of transformasional's leaderships which is 0,001 of transactional's leadership which is 0,022. Implication of this research is styled transformasional's leadership and transactional carries the wind on duty ascendant to ala clerk performance simultan. Key words : Transformasional's leadership, Transactional's leadership, ii performances